Sistem Pemasaran Kopi Robusta di Kota Pagar Alam, Sumatera Selatan - Malenda Malenda; Rita Nurmalina; Nia Rosiana (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2024)
Robusta coffee is a major commodity cultivated in Pagar Alam City. Coffee production increased by 65,1 percent from 2020 to 2021 is experiencing problems weak bargaining position of farmers in determining prices. This study aims to analyze the Robusta coffee marketing system in Pagar Alam City using market structure, market conduct, and market performance approaches. Determination of the farmer’s sample using purposive sampling method which identified 80 farmer respondents and 15 marketing agency respondents using the snowball sampling method. The structure of the Robusta coffee market in Pagar Alam City indicates an oligopoly. The Robusta coffee market faces a concentrated market with little competition indicating barriers to market entry. This is shown by the CR4 value of 0,64 where there are barriers to entry with an average MES (Minimum Efficiency Scale) value from 2018 to 2022 with a value of 12,1 percent. Robusta coffee marketing channels involve farmers and marketing institutions such as collecting traders, cooperatives and industries. Marketing channel 1 is relatively efficient where the marketing margin has the smallest value 37,78 percent and the farmer's share value with the highest value is 62,22 percent. Efforts to overcome an inefficient marketing system include disseminating market information through applications and websites, adding value to products, and forming farmer groups. Cooperatives provide credit facilities and enter into a contract system with farmers